Back to the Future: A Report From the 16th International Forum for Back and Neck Pain Research in Primary Care and Updated Research Agenda. Issue 19 (1st October 2022) - Dionne, Clermont E.; Rossignol, Michel; Deyo, Richard A.; Koes, Bart; Schoene, Mark; Battié, Michele
Abstract : Study Design: The 16th meeting of the International Forum for Back and Neck Pain Research in Primary Care was held in Québec City in July 2019 under the theme of innovation. This paper addresses the state of research in the field. Objective: To ascertain the evolution of knowledge and clinical application in back and neck pain and identify shifting research priorities. Materials and Methods: After a brief presentation of the Forum and its history, the current state of the field was depicted from the scientific program and the recordings of the plenary and parallel oral and poster communications of Forum XVI. Research agendas established in 1995 and 1997 were updated from a survey of a multidisciplinary group of experts in the field. A discussion of the progress made and challenges ahead follows. Results: While much progress has been made at improving knowledge at managing back pain in the past 25 years, most research priorities from earlier decades are still pertinent. The need for integration of physical and psychological interventions represents a key challenge, as is the need to better understand the biological mechanisms underlying back and neck pain to develop more effective interventions. Stemming the tide of back and neck pain in low and middle-income countries and avoiding the adoption of low-value interventions appear particularly important. The Lancet Low Back Pain Series initiative, arising from the previous fora, and thoughts on implementing best practices were extensively discussed, recognizing the challenges to evidence-based knowledge and practice given competing interests and incentives. Conclusion: With the quantity and quality of research on back and neck pain increasing over the years, an update of research priorities helped to identify key issues in primary care.